Food for thought: The underutilized potential of tropical tree‐sourced foods for 21st century sustainable food systems. Issue 4 (4th November 2020) - Jansen, Merel; Guariguata, Manuel R.; Raneri, Jessica E.; Ickowitz, Amy; Chiriboga‐Arroyo, Fidel; Quaedvlieg, Julia; Kettle, Chris J.
Abstract: The global food system is causing large‐scale environmental degradation and is a major contributor to climate change. Its low diversity and failure to produce enough fruits and vegetables is contributing to a global health crisis. The extraordinary diversity of tropical tree species is increasingly recognized to be vital to planetary health and especially important for supporting climate change mitigation. However, they are poorly integrated into food systems. Tropical tree diversity offers the potential for sustainable production of many foods, providing livelihood benefits and multiple ecosystem services including improved human nutrition. First, we present an overview of these environmental, nutritional and livelihood benefits and show that tree‐sourced foods provide important contributions to critical fruit and micronutrient (vitamin A and C) intake in rural populations based on data from sites in seven countries. Then, we discuss several risks and limitations that must be taken into account when scaling‐up tropical tree‐based food production, including the importance of production system diversity and risks associated with supply to the global markets. We conclude by discussing several interventions addressing technical, financial, political and consumer behaviour barriers, with potential to increase the consumption and production of tropical tree‐sourced foods, to catalyse a transition towards more sustainable global food systems. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Resumen: El sistema alimentario mundial está provocando una degradación ambiental a gran escala y es uno de los más importantes causantes del cambio climático. Su baja diversidad e incapacidad de producir suficientes frutas y verduras contribuye a generar una crisis de salud mundial. Se reconoce cada vez más que la extraordinaria diversidad de especies de árboles tropicales es vital para la salud planetaria y para apoyar la mitigación del cambio climático. Sin embargo, la diversidad de árboles tropicales está poco integrada en los sistemas alimentarios. La diversidad de árboles tropicales ofrece potencial para la producción sostenible de muchos alimentos, proporcionando beneficios para los medios de vida y la provisión de múltiples servicios de los ecosistemas y mejorar la nutrición humana. En primer lugar, presentamos una descripción general de estos beneficios ambientales, nutricionales y para los medios de vida y mostramos que los alimentos de origen arbóreo aportan importantes contribuciones a la ingesta de frutas y micronutrientes (vitamina A y C) para las poblaciones rurales. Luego, discutimos algunos riesgos y limitaciones que deben tenerse en cuenta al escalar la producción de alimentos basada en árboles tropicales, incluida la importancia de la diversidad del sistema de producción y los riesgos asociados con el suministro a los mercados mundiales. Concluimos con una discusión de las varias intervenciones que se necesitan para abordar los obstáculos técnicos, financieros, políticos y de comportamiento del consumidor, con posibilidades de aumentar el consumo y la producción de alimentos de origen arbóreo del trópico y promover una transición hacia sistemas alimentarios más sostenibles.